2017
DOI: 10.1177/0891988717700507
|View full text |Cite
|
Sign up to set email alerts
|

Dysexecutive Symptoms in Primary Progressive Aphasia: Beyond Diagnostic Criteria

Abstract: Primary progressive aphasia (PPA) is a heterogeneous neurodegenerative condition in which the most prominent clinical feature is language difficulties. Other cognitive domains have been described to remain unaffected at the early stages of the disease and, therefore, excluded from diagnostic criteria. However, we show in this article that executive function (EF) disorders may be present in the 3 variants (nonfluent/agrammatic, logopenic, and semantic) of PPA. We also illustrate changes in language and EF by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
29
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 83 publications
9
29
0
1
Order By: Relevance
“…This is consistent with previous reports suggesting that patients with PPA due to AD have greater memory, visuospatial, and executive impairment than other PPA variants. 6972 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with previous reports suggesting that patients with PPA due to AD have greater memory, visuospatial, and executive impairment than other PPA variants. 6972 …”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous reports suggesting that patients with PPA due to AD have greater memory, visuospatial, and executive impairment than other PPA variants. [69][70][71][72] Strengths of this study include the large sample size (n = 1,251) from 36 centers, and the inclusion of various measures of Aβ pathology (CSF, PET, and autopsy). Our study also has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…First, although one might expect individuals with semantic deficits to have difficulty understanding complex task instructions, it is unclear why SD patients would have more difficulty than SA patients when they are often matched in performance on semantic tasks. Second, many studies outside of the storage-access literature have reported success in testing SD patients on various executive tasks (e.g., Bozeat, Gregory, Lambon Ralph, & Hodges, 2000a;Butts et al, 2015;Desgranges et al, 2007;George & Mathuranath, 2005;Gorno-Tempini et al, 2004;Libon et al, 2007;Macoir, Lavoie, Laforce, Brambati, & Wilson, 2017;Perry & Hodges, 2000). Furthermore, some of these studies have shown SD patients to have executive deficits (e.g., on trail-making and Stroop tasks; Butts et al, 2015;Desgranges et al, 2007;George & Mathuranath, 2005;Gorno-Tempini et al, 2004;Libon et al, 2007;Macoir et al, 2017).…”
Section: Executive Impairments and Correlations With Semantic Performmentioning
confidence: 99%
“…Studies documenting executive deficits in SD patients have suggested that SD patients may be more similar to SA patients on EF than is typically claimed. That is, although atrophy in SD occurs predominately in the anterior temporal lobes and spreads posteriorly as the disease progresses (Collins et al, 2017;Galton et al, 2001;Gorno-Tempini et al, 2011), frontal atrophy is found in SD in both cross-sectional (Cerami et al, 2017;Mummery et al, 2000) and longitudinal (Brambati et al, 2015;Brambati et al, 2009;Kumfor et al, 2016;Macoir et al, 2017) studies, even relatively early in disease progression (Borroni et al, 2007;Gorno-Tempini et al, 2004;Rosen et al, 2002). Fronto-temporal white matter tracts also appear to be typically affected in SD (Agosta et al, 2010;Brambati et al, 2015), and connectivity studies have shown reduced strength in executive networks (Farb et al, 2013).…”
Section: Executive Impairments and Correlations With Semantic Performmentioning
confidence: 99%
“…Executive impairments may be encountered in the early or more advanced stages of lvPPA, when atrophy extends to adjacent brain areas [28]. Short-term phonologic memory deficits may explain why lvPPA subjects performed poorly on higher executive functioning tasks which engage the verbal working memory system [29].…”
Section: Discussionmentioning
confidence: 99%